Combined analysis of lipidomics and transcriptomics revealed the key pathways and genes of lipids in light-sensitive albino tea plant (Camellia sinensis cv. Baijiguan) - Zhou, Zhe; Chen, Mingjie; Wu, Quanjin; Zeng, Wen; Chen, Zhidan; Sun, Weijiang (Frontiers in Plant Science, 2022)
At present, the mechanism by which light-sensitive albino tea plants respond to light conditions to regulate pigment synthesis has been partially elucidated. However, few studies have focused on the role of lipid metabolism in the whitening of tea leaves. Therefore, in our study, the leaves of the Baijiguan (BJG) tea tree under shading and light restoration were analyzed by the combination of lipidomics and transcriptomics. The leaf color of BJG was regulated by light intensity and responded to light changes by changing lipid content and proportion. According to the correlation analysis, we also obtained three key lipid components that were significantly correlated with chlorophyll SPAD value, namely MGDG (36:6), DGDG (36:6) and DGDG (34:3). Further weighted gene co-expression network (WGCNA) analysis showed that HY5 TF and GLIP genes may be hub genes involved in lipid regulation of albino tea leaves. Our results lay a foundation for further explanation of the color change of albino tea leaves.